Effects of Brx-019 (Acetic Acid 3,6a,9-triacetoxy-6,6a,7,11b-tetrahydro-indeno [2,1-c]chromen-10-yl Ester), a Brazilin Derivative, on T Cell-mediated Immune Responses in Multiple Low Dose Streptozo-tocin-induced Diabetic C57BL/6 Male Mice - Kwak, Wie-Jong; Kim, Min-Hwa; Jeon, Sun-Duck; Khil, Lee-Yong; Chae, Sang-Ho; Kim, Deukjoon; Lee, Byung-Hoon; Moon, Chang-Kiu (Arzneimittelforschung, 2005)
Brx-019 (acetic acid 3,6a,9-triacetoxy-6, 6a,7,11b-tetrahydro-indeno[2,1-c] chromen-10-yl ester) was derived from brazilin (CAS 474-07-7) during a trial designed to search for immunomodulators with lower toxicity and more effective immunomodulating activities than brazilin. Brx-019 was selected as a potential immunomodulator based on its effects on Concanavalin A (Con A)-induced proliferation of splenocytes and the 3-[4,5-dimethylthiazol-2-yl]-2,5-diphenyltetrazolium bromide (MTT) assay.Intraperitoneally administered Brx-019 significantly improved delayed type hypersensitivity and increased immunoglobulin M (IgM) plaque forming cells (PFCs) in multiple low dose streptozotocin-induced diabetic mice (MLDS-diabetic mice). This finding suggests that Brx-019 may increase suppressed humoral and cell-mediated immunity in type 1 diabetes. Brx-019 also significantly increased Con A- or alloantigen-induced proliferation of splenocytes, Con A-induced interleukin 2 (IL-2) production from splenocytes, and IL-2-induced proliferation of Con A-activated splenocytes in MLDS-diabetic mice. These results suggest that Brx-019 might improve immunity in diabetic mice by increasing IL-2 production in splenocytes and responsiveness of splenocytes to IL-2, which were suppressed in MLDS-diabetes.
Keywords: Brazilin, derivative; Brx-019, delayed type hypersensitivity, splenocytes proliferation, T cell-mediated immune response; CAS 474-07-7; Immunomodulator